Strengthening The Downstream of Robusta Coffee Products in Gunungjaya Village, Salem Sub-District, Brebes District - undri rastuti; purwati; purwanto; ary yunanto; siti badiatul umroh; sutarmin (Journal of Society, Community and Business Development, 2023)
Gunung Jaya Village, Salem District, there is a Joint Business Group (KUB) "Lulumpang". Previously, the Lulumpang KUB in Gunung Jaya Village, Salem Subdistrict, Brebes Regency carried out the process of peeling cherry coffee manually using mortar and pestle. This process is time-consuming and labor-intensive, resulting in many broken beans. In addition, stripping the dry skin is also still with lumpang-alu, of course this is very time consuming and hampers the production process. "Lulumpang" also does not have an adequate drying room and drying equipment, so if there is an abundance of harvest, they are overwhelmed. Based on some of the problems faced by KUB Lulumpang as a partner, the pengabdi will handle through 3 stages of service that will be carried out in 3 years, namely year 1 focusing on cultivation and post-harvest technology. In this first year, the service program has been carried out in the form of handling post-harvest technology through training and grants of wet skin peeling tools, namely pulper. In the 2nd year, this service focuses on increasing the production and quality of raosted beans. After the General Soedirman University service team conducted counseling and workshops, the roasted bean production capacity increased 5X and group members increasingly understood the importance of quality control and procedures for saving failed products.